Synthesis and evaluation of some novel heterocyclic compounds containing Pyrimidine and Thiazolidinone rings and their Derivatives as an antimicrobial agents - Ganesh S Andhale; Sapana M Nagare; SR Pattan; Krishna Kumar K L (International Journal of Pharmacy and Analytical Research, 2022)
A series of (4, 6-disubstituted phenyl) pyrimidine and their derivatives are known for their biological importance. In present research work, we have attempted both Conventional to synthesize 1- (4, 6-disubstituted phenyl) pyrimidin-2yl-2-(4methoxyphenyl) thiazolidine-4-one. A wide spectrum of biological activities like anti-diabetic, anti-bacterial, antifungal, anti-oxidant and anti-inflammatory activities are found to be associated with pyrimidine nucleus. Chalcones were synthesized by claisen -schmidt reaction using aromatic aldehydes and ketones. Then reacting with guanidine hydrochloride the resultant pyrimidine compounds are synthesized. Again its Schiff’s base reaction is carried out and then cycloaddition reaction is done, so (4, 6 -disubstituted phenyl) pyrimidin-2 yl-2-(4methoxyphenyl) thiazolidine-4-one derivatives are prepared by using thioglycolic acid. All the synthesized compounds were characterized by IR were recorded for all compo unds, 1H-NMR and Elemental Analysis was carried out for prototype of compounds. All the compounds were evaluated for antibacterial (S. aureus and E. coli) activity and antifungal (A. niger and C. albicans) activity at the concentration of 100 µg/mL by using cup-plate agar diffusion method. The activity was measured in terms of zone of inhibition and compared with standard drug Ciprofloxacin for antibacterial activity and Griseofulvin for antifungal activity.